Analysis of visual strategies in highly-qualified handball players during the performance of penalty throws - Jedziniak, W.; Florkiewicz, B.; Zwierko, T. (Journal of Kinesiology and Exercise Sciences, 2016)
Aim. The main aim of this study was to evaluate the visual strategy of players performing a penalty throw in handball and the analysis of the relationship between the assumed strategy and throw effectiveness. Material and methods. The study group consisted of 12 highly-qualified handball players, aged 24.08 ± 5.82 years. For the evaluation of eye movements, we used a mobile eye-tracking system in the form of glasses and an image recording controller (SMI ETG 2w, Germany). The participants performed 5 penalty throws in conditions specified by the rules of the game. We evaluated the time and number of fixations, time of maintaining visual stability and localization in relation to specified targets, i.e. the goal, the goalkeeper. Results. Analysis of the results showed, among others, that (1) throw effectiveness is not related to the temporal (H = 3.085, p = 0.079) or numerical (H = 2.895, p = 0.088) parameters of fixation during a penalty throw, (2) visual observation of the goalkeeper, particularly areas of the head and torso, had positive impact on throw effectiveness (H = 5.005, p = 0.025) during the preparatory phase of a throw, (3) the last points of fixation on the goal before performing the penalty throw during the proper phase positively correlates with the effective throws (Chi2 = 6.28, p = 0.043). Conclusions. The strategy of visual behaviours during the performance of penalty throws in handball is to a greater extent associated with visual localization than temporal and numerical parameters of the conducted fixations. The type of adopted visual strategy in relation to throw effectiveness is different in the preparatory phase than during the proper phase of a throw.